Implementasi Penulisan Buku Referensi pada Mahasiswa/i Universitas Budi Darma Medan - Matias Julyus Fika Sirait; Denni M Rajagukguk (Cattleya Darmaya Fortuna, 2024)
This study aims to evaluate the implementation of reference book writing for students of Budi Darma University Medan as an active learning method. Reference book writing is considered as a form of active learning that can improve students' material understanding, research skills, and academic writing. The research method used was a mixed approach, involving surveys, interviews, observations, and document analysis to collect data from students and lecturers involved. The results showed that reference book writing had a significant positive impact on students' material understanding, research skills, and academic writing ability. Most students reported improved understanding and skills after engaging in the project. However, there were some challenges, including difficulties in team coordination, high workload, and problems in editing the material. The discussion revealed that the reference book writing method was effective in deepening students' understanding of the material and improving their academic skills. Nonetheless, the challenges encountered point to the need for better project management strategies and consistent mentorship support. In conclusion, reference book writing as an active learning method proved effective in improving students' academic skills at Universitas Budi Darma Medan. To maximize the results, it is recommended that the university provide additional training, more intensive guidance, and effective project management guidelines. This research provides valuable insights into the implementation of active learning methods and provides recommendations for improvement in its application in higher education.